Shortlasting, Unilateral, Neuralgiform, Headache Attacks with Conjunctival Injection, Tearing, Sweating and Rhinorrhea: The Term and New View Points - Antonaci, Fabio; Fredriksen, Torbjørn; Pareja, Juan A.; Sjaastad, Ottar (Frontiers in Neurology, 2018)
A solitary patient with symptoms similar to those of SUNCT was first mentioned in 1978. The term SUNCT was first used in 1991. SUNCT is an acronym; the "S" signifies "Shortlasting"; the "U" symbolizes "Unilateral"; "N" stands for "Neuralgiform"; the "C" for "Conjunctival injection"; and "T" for "Tearing". The term SUNA was marketed in 2004. The terminology and new view points are discussed and nosography proposal for SUNCT is presented.